Government at work - Schull, Rebecca (Bold Face Books; distributed by Sterling Pub. Co., 1967)
An explanation of the mechanics of the U.S. government. Gives a brief analysis of each agency in the three Government branches and describes their individual function as well as their contribution to the whole.